Degeneration of the Suprachiasmatic Nucleus in an Alzheimer's Disease Mouse Model Monitored by in vivo Magnetic Resonance Relaxation Measurements and Immunohistochemistry - Roy, Upasana; Heredia-Muñoz, Mónica T; Stute, Lara; Höfling, Corinna; Matysik, Jörg; Meijer, Johanna H; Roßner, Steffen; Alia, A (Journal of Alzheimer's disease, 2019)
In Alzheimer's disease (AD), disturbances in the circadian rhythm and sleep-wake cycle are frequently observed. Both are controlled by the master clock: the suprachiasmatic nucleus (SCN), which was reported in postmortem studies of AD subjects to be compromised. However, the influence of age and gender on the biophysical integrity and subtle microstructural changes of SCN and mechanistic connections between SCN dysfunction and AD progression in vivo remain to be explored. In the present study, we utilized state-of-the-art in vivo magnetic resonance relaxation measurements in combination with immunohistochemistry to follow microstructural changes in SCN of the Tg2576 mouse model of AD. Longitudinal monitoring of in vivo T2 relaxation with age shows significant shortening of T2 values in the SCN of transgenic mice and more substantially in female transgenic than aged-matched controls. Multiexponential T2 analysis detected a unique long T2 component in SCN of transgenic mice which was absent in wild-type mice. Immunohistochemical examination revealed significantly elevated numbers of activated astrocytes and an increase in the astrocyte to neuron ratio in SCN of transgenic compared to wild-type mice. This increase was more substantial in female than in male transgenic mice. In addition, low GABA production in SCN of transgenic mice was detected. Our results offer a brief appraisal of SCN dysfunction in AD and demonstrate that inflammatory responses may be an underlying perpetrator for the changes in circadian rhythmicity and sleep disturbance in AD and could also be at the root of marked sex disparities observed in AD subjects.